Sevoflurane Induces Ferroptosis of Glioma Cells Through Activating the ATF4-CHAC1 Pathway - Xu, Yingyi; Zhang, Na; Chen, Cheng; Xu, Xinke; Luo, Ailing; Yan, Yaping; Lu, Yanhua; Liu, Jianhua; Ou, Xinxu; Tan, Yonghong; Liang, Yufeng; Chen, Lihe; et al. (Frontiers in Oncology, 2022)
Objective: To clarify the function of Sevoflurane (Sev) on ferroptosis and explore the mechanisms in glioma cells. Methods: Different concentration of Sev was used to treat glioma cells U87 and U251. Ferroptosis inducer Erastin was used to incubate with glioma cells combined with Sev and ATF4 siRNA transfection treatment. CCK-8 assay and colorimetric assay were performed to analyze cell viability and Fe+ concentration, respectively. The releases of reactive oxygen species (ROS) were determined by flow cytometry analysis. Transcriptional sequencing was used to screening the differential genes affected by Sev in U251 cells. The mRNA and protein expression associated with ferroptosis was detected by qRT-PCR and Western blotting. Results: Sev could suppress cell viability, increased ROS levels, Fe+ concentration, downregulated the protein expression levels of GPX4 and upregulated transferrin, ferritin, Beclin-1 in a dose-dependent manner in U87 and U251 cells. Sev could induce ferroptosis and mitophagy-related gene ATF4 and its downstream CHAC1 expression in glioma cells identified by transcriptional sequencing. Moreover, suppressing ATF4 expression could interrupt Sev-induced ferroptosis and CHAC1 activating, which could be reversed by Erastin in glioma cells. Conclusions: In summary, this study suggested that Sev exposure-induced ferroptosis by ATF4-CHAC1 pathway in glioma cells.